2020
DOI: 10.1016/j.marpetgeo.2020.104397
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry of the South China Sea conjugate margins in a rifting, drifting and collision context

Abstract: The symmetry of conjugate rifted margins is a first-order observable feature reflecting the geodynamic processes acting during and after continental rifting. The symmetry of the South China Sea (SCS) rifted margins can be deduced from comprehensive geophysical datasets on a continental-margin scale. Here, we combine three key approaches: (1) lateral fault distributions are delineated according to free-air gravity anomalies, (2) crustal stretching styles are mapped based on gravity inversion constrained by deep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 97 publications
(121 reference statements)
2
7
0
Order By: Relevance
“…We suggested extension of the spreading axis only few kilometers onshore into Sabah consistent with data from Pilia et al (2021). ( 4) The free-air gravity anomaly map of Bai et al (2020) shows a negative anomaly at the extension of the Sulu trench in Sabah. This could be an indication of significant crustal thinning and asthenosphere upwelling similar to the Sulu and South China Sea, in accordance with our interpretation.…”
supporting
confidence: 74%
“…We suggested extension of the spreading axis only few kilometers onshore into Sabah consistent with data from Pilia et al (2021). ( 4) The free-air gravity anomaly map of Bai et al (2020) shows a negative anomaly at the extension of the Sulu trench in Sabah. This could be an indication of significant crustal thinning and asthenosphere upwelling similar to the Sulu and South China Sea, in accordance with our interpretation.…”
supporting
confidence: 74%
“…A ductile layer is probably required underneath the detachment fault to accommodate the subsidence at the depocenter (Fig. 13b) as interpreted previously in adjacent Qiongdongnan Basins and Xisha Trough (Clift et al, 2002;Davis and Kusznir, 2004;Pichot et al 2014, Lei andRen, 2016;Xie et al, 2019;Lei et al, 2019;Bai et al, 2020). This could favor the depth-dependent decoupling as suggested in several simulations in the case of wide rifted margins (Huismans and Beaumont, 2011;Lin, 2001, Brune et al, 2017;Ros et al, 2017).…”
Section: Break-up Evolution In the Sw Marginsupporting
confidence: 58%
“…In the north, Xisha Islands margin based on correlation with seismic profiles tied with wells in adjacent Phu Khanh and Qiongdongnan basins (Vu et al, 2017;Savva et al, 2013;Lei and Ren, 2016), which is identified an unconformity around 32 Ma (T70) and the BU at 23 Ma (T60). In the south, it shares a similar rifting history with the northern margin during the Paleogene (Holloway, 1982;Liang et al, 2019;Bai et al, 2020;Zhang et al, 2020b). The age constraint is established on the base of the well Sampaguita-1 continuously documenting Cenozoic strata and encountering the Mesozoic strata (location S-1 on Figs.…”
Section: Interpretation Criteriamentioning
confidence: 93%
See 1 more Smart Citation
“…(4) Regional gravity data (Fig. 1) do not support extending the Sulu Sea southwest rift under Sabah (Cullen et al, 2012;Bai et al, 2020). ( 5 Ultramafic rocks are normally devoid of primary zircons, but zircon can crystallize in ophiolitic rocks during hydrothermal alteration (Dubińska et al, 2004;Schaltegger, 2007).…”
mentioning
confidence: 99%